2011
DOI: 10.1371/journal.pone.0022938
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of HvCBF Genes and Their Association with Salinity Tolerance in Tibetan Annual Wild Barley

Abstract: The evaluation of both the genetic variation and the identification of salinity tolerant accessions of Tibetan annual wild barley (hereafter referred to as Tibetan barley) (Hordeum vulgare L. ssp. Spontaneum and H. vulgare L. ssp. agriocrithum) are essential for discovering and exploiting novel alleles involved in salinity tolerance. In this study, we examined tissue dry biomass and the Na+ and K+ contents of 188 Tibetan barley accessions in response to salt stress. We investigated the genetic variation of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
59
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 64 publications
9
59
0
1
Order By: Relevance
“…For example, in our previous study, we identified elite salt-tolerant genotypes from around 200 accessions of Tibetan wild barley (e.g. XZ16 and XZ26), showing a better salinity tolerance than CM72, a well-known salt-tolerant cultivar [12]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in our previous study, we identified elite salt-tolerant genotypes from around 200 accessions of Tibetan wild barley (e.g. XZ16 and XZ26), showing a better salinity tolerance than CM72, a well-known salt-tolerant cultivar [12]. …”
Section: Introductionmentioning
confidence: 99%
“…So far, many physiological parameters were used to identify salt tolerance, including relative root length [14], leaf cell elongation [15], relative dry weights of shoots and roots [10, 12], Na and K contents [16, 17], and K/Na ratio [18, 19]. Among these traits, relative shoot dry weight might be a more real and reliable trait for reflecting plant growth under salt stress, as shoot growth is generally more sensitive than root growth in response to salinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that wild barley contained special germplasm with high tolerance to abiotic stresses, such as salinity and drought (Zhao et al, 2010;Wu et al, 2011). The current study showed that Tibetan wild barleys have wide genetic variation in BAA and BAT.…”
Section: Discussionmentioning
confidence: 55%
“…Recent technological advances have seen the development of the “omics” technologies which are being applied in plant sciences to identify key proteins or metabolites, are novel covering metabolomics, proteomics and, genomics responsible for plants stress tolerance and also the genes regulating such biomolecules (Ahmad et al, 2013; Shelden et al, 2013; Srivastava et al, 2013; Emon, 2016). Application of these omics facilitates a direct observation of the agents affecting plant development.…”
Section: Introductionmentioning
confidence: 99%